Cognitive Behavioral Psychotherapies: History and Development - M. Hakan Türkçapar; A. Emre Sargın (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Cognitive behavioral therapies are one of the most leading theories between current psychotherapies. As a psychotherapy school, besides sharing the common points reached collectively by the humanity throughout the history, it also achieved in integrating scientific and ampirical experiences into the psychotherapy practice. Having included mainstreams like Stoicism, Kantian philosopy in its historical roots, this approach has similarities with eastern philosophies, budism and sufism. Apart from its historical and cultural roots, cognitive approach integrated with behaviorism which applied scientific method in human psychology for the first time, and also implemented the scientific method in the cognitive field. Cognitive behavioral approaches shall make important contributions in the pathway that psychotherapies will cover.